All- trans retinoic acid inhibited angiotensin II-induced increase in cell growth and collagen secretion of neonatal cardiac fibroblasts - He Yan; Huang Ying; Zhou Li; Lu Li-min; Zhu Yi-chun; Yao Tai (Acta Pharmacologica Sinica, 2016)
Aim: To determine whether all-trans retinoic acid (at RA) acts to modulate angiotensin II (Ang II)-induced cardiac fibroblast cell growth and collagen secretion. Methods: Cultured neonatal rat cardiac fibroblasts (CF) were used in the experiment. A 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay was used to detect cell growth of the CF; and immunocytochemistry and Western blotting were used to measure the production and secretion of collagen and the expression of transforming growth factor-β1 (TGF-β1) by the CF. Results: at RA (1×10-7 to 1×10-5 mol/L) inhibited the Ang II-induced increase in cell growth of CF (P